Alcohol-Drinking Under Limited-Access Procedures During Mature Adulthood Accelerates the Onset of Cognitive Impairment in Mice - Jimenez Chavez, C. Leonardo; Van Doren, Eliyana; Matalon, Jacob; Ogele, Nneoma; Kharwa, Aadithya; Madory, Lauren; Kazerani, Ida; Herbert, Jessica; Torres-Gonzalez, Jose; Rivera, Emely; Szumlinski, Karen K. (Frontiers in Behavioral Neuroscience, 2022)
A history of heavy drinking increases vulnerability to, and the severity of, Alzheimer’s Disease (AD) and related dementias, with Alcohol Use Disorder (AUD) identified as the strongest modifiable risk factor for early-onset dementia. Heavy drinking has increased markedly in women over the past 10 years, with mature adult women reporting a 41% increase in heavy drinking days during the coronavirus (COVID-19) pandemic. This raises concern over the impact of excessive alcohol consumption during mature adulthood on dementia-related outcomes in both the short- and long-term. As a first pass attempt at addressing this issue, the present study employed isogenic and congenic female and male mature adult (5-9 months of age) C57BL/6J (B6J) mice to examine how a 1-month history of alcohol intake under modified Drinking-in-the-Dark (DID) procedures (10, 20,40% alcohol v/v) alters spatial and working memory. In both a genetically and experientially heterogeneous cohort of mice and in an isogenic B6J cohort, mature adult female mice consumed more alcohol than their male counterparts, with alcohol intake escalating over the 1-month drinking-period. In both cohorts, a DID history impaired the ability of mice to locate a visible platform in the Morris maze, while DID isogenic B6J females also exhibited impaired spatial recall and DID males from the heterogeneous cohort exhibited impaired reversal learning. In the radial arm maze, DID females in both cohorts required more training to acquire the platform locations and committed more reference or working memory incorrect errors than their female water controls. These data indicate that alcohol consumption during mature adulthood produces mild, but behaviorally impactful, changes in cognitive function to which females are more sensitive. If relevant to humans, these findings demonstrate that binge-like drinking by mature adults, women in particular, is sufficient to induce immediate and persistent cognitive impairment, which may predispose individuals to dementia